Who Counts? - Smith, David H. (Journal of religious ethics, 1984)
Many issues in medical ethics seem to turn on arguments about the moral status of some human beings. This essay criticizes attempts to make clear distinctions proposed by Engelhardt, Green/Wikler, Becker, and Brody. The author suggests that the theories discussed divert attention from more resolvable problems.